56.2k views
2 votes
7(x+4)+1x-9*2= -8x+-10
Please show steps

2 Answers

6 votes

Answer:


Explanation:

7(x+4)+1x-9*2=-8x+-10 first remove parenthesis

7x+28+x-9*2=-8x-10 then do the multiplication

7x+28+x-18=-8x-10 now combine like terms

8x+10=-8x-10 add 8x to both sides

16x+10=-10 subtract 10 from both sides

16x=-20 divide by 16 on both sides

x= -20/16

User Rinaldi
by
4.8k points
6 votes

Answer:

-5/4

Explanation:

7(x + 4) + 1x - 9 * 2 = -8x + -10

Distribute 7 on left side. Multiply 9 * 2 on left side.

7x + 28 + 1x - 18 = -8x + -10

Combine like terms on left side.

8x + 10 = -8x + -10

Add 8x to both sides. Subtract 10 from both sides.

16x = -20

Divide both sides by 16.

x = -20/16

Reduce the fraction.

x = -5/4

User Wisnu Wijokangko
by
5.8k points